1998
DOI: 10.1097/00001756-199811160-00001
|View full text |Cite
|
Sign up to set email alerts
|

Endurance training increases acetylcholine receptor quantity at neuromuscular junctions of adult rat skeletal muscle

Abstract: The aim of the study was to test the hypothesis that a 16 week endurance training program would alter the abundance of endplate-associated nicotinic acetylcholine receptors (nAChR) in various rat skeletal muscles. We found a 20% increase in endplate-specific [125I]alpha-bungarotoxin binding in several muscles of trained rats, accompanied by equal susceptibility of toxin binding to the inhibitory effect of D-tubocurarine in sedentary and trained muscles. We conclude that the neuromuscular junction adaptations t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Maffiuletti et al (2001) recently demonstrated that the absolute amplitude of the H-reflex was larger in endurance-trained than in either sedentary or strength-trained subjects, whereas the peak torque of the twitch evoked by that stimulation was lower in the endurance-trained group. In addition, the trained muscle fibre has greater density and sensitivity of acetylcholine receptors at the motor endplate (Desaulniers et al 1998), thus augmenting the generation of a post-synaptic potential. Similarly, a greater density of Na + /K + pumps in the muscle fibre membrane of endurance-trained muscle (McKenna et al 1996) may allow action potentials to propagate along the muscle fibre membrane with less distance-related decay in amplitude.…”
Section: Discussionmentioning
confidence: 99%
“…Maffiuletti et al (2001) recently demonstrated that the absolute amplitude of the H-reflex was larger in endurance-trained than in either sedentary or strength-trained subjects, whereas the peak torque of the twitch evoked by that stimulation was lower in the endurance-trained group. In addition, the trained muscle fibre has greater density and sensitivity of acetylcholine receptors at the motor endplate (Desaulniers et al 1998), thus augmenting the generation of a post-synaptic potential. Similarly, a greater density of Na + /K + pumps in the muscle fibre membrane of endurance-trained muscle (McKenna et al 1996) may allow action potentials to propagate along the muscle fibre membrane with less distance-related decay in amplitude.…”
Section: Discussionmentioning
confidence: 99%
“…9,11 Consequently, to increase the number of receptors at the endplate, an increase in post-synaptic area is necessary. Such an enhancement of ACh receptor number per endplate may have important functional benefits.…”
Section: Discussionmentioning
confidence: 99%
“…14,24 This ongoing remodeling of the adult NMJ appears to be amplified by increased neuromuscular activity. Several studies have documented that exercise training, over a period of several weeks, can alter several parameters of NMJ architecture including size, 2,11,22 length, 12,22 dispersion of synaptic vesicles and receptors, 9 and nerve terminal branching 2,11,12 in adult mammals. In all of the investigations conducted to date, treadmill running, featuring repetitive neuromuscular activation of long continuous duration, has been utilized to present the exercise stimulus.…”
mentioning
confidence: 99%
“…Nicotinic AChRs (nAChRs) are ligand‐gated ion channels formed by pentameric arrangements of α and β subunits, which based on their sensitivity to α‐BTX and nicotine can be subdivided in two large families [74]. Endurance training increases the abundance of endplate‐associated nAChRs that are sensitive to α‐BTX [75]. Data collected in several tissues and under different conditions indicate that the nocturnal melatonin surge increases the number and/or potentiates the effects mediated by nAChRs sensitive to α‐BTX (reviewed in [76]).…”
Section: Melatonin and Physical Performancementioning
confidence: 99%